An empirical study on general insurance agents' performance in Sri Lankan insurance industry - Muthusamy, V. (Faculty of Management Studies & Commerce, University of Jaffna, 2018)
The confrontational thoughts and poor risk management knowledge has been lead to a complex competitive environment Sri Lankan general insurers. The general public trust on insurance industry became a major problem for the development of the general insurance industry. The insurance regulator of the insurance industry evidenced through the statistical data that general insurance industry has not developing in a desirable growth rate. The penetration has been extremely low for many years. The insurance companies' existence depends on their competent human resources, especially the agents. Thus, the general insurers attempt to concentrate on sales agents performances to improve the company sales to capture a significant market share. Therefore, this study pertained to explore the existing relationship between sales persons skills and agents performance in general insurance industry in Sri Lanka. The study was utilized quantitative method by using questionnaires to randomly select 331 insurance advisors from general insurance industry. The study selected selling skill dimensions (Interpersonal Skills, Salesmanship Skills, Technical Skills, Marketing Skills) as dependent variables and salesperson sales performance as independent variables. The study confirmed interpersonal skill most influencing factor on sales person performance.
Keywords: Insurance; Selling skill; Sales performance; Relationship